Dissolved organic matter in soils varies across a chronosequence of Pinus massoniana plantations. Issue 4 (13th April 2017) - Justine, Meta Francis; Yang, Wanqin; Wu, Fuzhong; Tan, Bo; Naeem Khan, Muhammad; Li, Zhijie
Abstract: Stand age plays a significant role in forest ecosystems nutrient cycling. Unfortunately, less attention was accorded to the changes in dissolved organic matter (DOM) in soil layers of mono‐stand plantations. A field soil sampling experiment was conducted to examine the effects of forest age and soil depth on concentrations and distribution patterns of dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) in a chronosequence of 11 stands of Masson pine ( Pinus massoniana ) plantations. The soil total organic carbon (TOC) and soil total nitrogen (TN) were also investigated. Concentrations of DOC and DON varied with stand age and decreased significantly ( P  <   0.05) with depth from 503.9 to 337.1 mg/kg and from 67.9 to 45.0 mg/kg, respectively, between the 0‐ to 30‐ and 30‐ to 60‐cm soil layers. Dissolved organic carbon and DON were significantly correlated, the ratios of DOC to TOC and DON to TN increased significantly from 0.11 to 0.20 and 0.16 to 0.39 in the upper to the lower soil layer, whereas the TOC/TN ratio decreased significantly with stand age. Our results suggest that (1) soil C/N ratios decrease with stand age, (2) DOM concentration decreases with depth, (3) soil pH and moisture content affect DOM concentrations, and (4) DOM concentrations are influenced by export of organic matter from litter and the forest floor surface.